Implications of intratumoral microbiota in tumor metastasis: a special perspective of microorganisms in tumorigenesis and clinical therapeutics - Lei Zhang; Xichu Duan; Yanhua Zhao; Dejiu Zhang; Yuan Zhang (Frontiers in Immunology)
Tumor metastasis is the main cause of therapeutic failure and mortality in cancer patients. The intricate metastastic process is influenced by both the intrinsic properties of tumor cells and extrinsic factors, such as microorganisms. Notably, some microbiota have been discovered to colonize tumor tissues, collectively known as intratumoral microbiota. Intratumoral microbiota can modulate tumor progression through multiple mechanisms, including regulating immune responses, inducing genomic instability and gene mutations, altering metabolic pathways, controlling epigenetic pathways, and disrupting cancer-related signaling pathways. Furthermore, intratumoral microbiota have been shown to directly impact tumor metastasis by regulating cell adhesion, stem cell plasticity and stemness, mechanical stresses and the epithelial-mesenchymal transition. Indirectly, they may affect tumor metastasis by modulating the host immune system and the tumor microenvironment. These recent findings have reshaped our understanding of the relationship between microorganims and the metastatic process. In this review, we comprehensively summarize the existing knowledge on tumor metastasis and elaborate on the properties, origins and carcinogenic mechanisms of intratumoral microbiota. Moreover, we explore the roles of intratumoral microbiota in tumor metastasis and discuss their clinical implications. Ongoing research in this field will establish a solid foundation for novel therapeutic strategies and clinical treatments for various tumors.